Post-kala-azar dermal leishmaniasis (PKDL) drug efficacy study landscape: A systematic scoping review of clinical trials and observational studies to assess the feasibility of establishing an individual participant-level data (IPD) platform. - Sauman Singh-Phulgenda; Rishikesh Kumar; Prabin Dahal; Abdalla Munir; Sumayyah Rashan; Rutuja Chhajed; Caitlin Naylor; Brittany J Maguire; Niyamat Ali Siddiqui; Eli Harriss; Manju Rahi; Fabiana Alves; et al. (PLoS Neglected Tropical Diseases)
Background Post-kala-azar dermal leishmaniasis (PKDL) is a dermatosis which can occur after successful treatment of visceral leishmaniasis (VL) and is a public health problem in VL endemic areas. We conducted a systematic scoping review to assess the characteristics of published PKDL clinical studies, understand the scope of research and explore the feasibility and value of developing a PKDL individual patient data (IPD) platform. Methods A systematic review of published literature was conducted to identify PKDL clinical studies by searching the following databases: PubMed, Scopus, Ovid Embase, Web of Science Core Collection, WHO Global Index Medicus, PASCAL, Clinicaltrials.gov, Ovid Global Health, Cochrane Database and CENTRAL, and the WHO International Clinical Trials Registry Platform. Only prospective studies in humans with PKDL diagnosis, treatment, and follow-up measurements between January 1973 and March 2023 were included. Extracted data includes variables on patient characteristics, treatment regimens, diagnostic methods, geographical locations, efficacy endpoints, adverse events and statistical methodology. Results A total of 3,418 records were screened, of which 56 unique studies (n = 2,486 patients) were included in this review. Out of the 56 studies, 36 (64.3%) were from India (1983-2022), 12 (21.4%) from Sudan (1992-2021), 6 (10.7%) were from Bangladesh (1991-2019), and 2 (3.6%) from Nepal (2001-2007). Five (8.9%) studies were published between 1981-1990 (n = 193 patients), 10 (17.9%) between 1991-2000 (n = 230 patients), 10 (17.9%) between 2001-2010 (n = 198 patients), and 31 (55.4%) from 2011 onwards (n = 1,865 patients). Eight (14.3%) were randomised clinical trials, and 48 (85.7%) were non-randomised studies. The median post-treatment follow-up duration was 365 days (range: 90-540 days) in 8 RCTs and 360 days (range: 28-2,373 days) in 48 non-randomised studies. Disease diagnosis was based on clinical criterion in 3 (5.4%) studies, a mixture of clinical and parasitological methods in 47 (83.9%) and was unclear in 6 (10.7%) studies. Major drugs used for treatment were miltefosine (n = 636 patients), liposomal amphotericin B (L-AmB) (n = 508 patients), and antinomy regimens (n = 454 patients). Ten other drug regimens were tested in 270 patients with less than 60 patients per regimen. Conclusions Our review identified studies with very limited sample size for the three major drugs (miltefosine, L-AmB, and pentavalent antimony), while the number of patients combined across studies suggest that the IPD platform would be valuable. With the support of relevant stakeholders, the global PKDL community and sufficient financing, a PKDL IPD platform can be realised. This will allow for exploration of different aspects of treatment safety and efficacy, which can potentially guide future healthcare decisions and clinical practices.